2022
DOI: 10.3390/cancers14174318
|View full text |Cite
|
Sign up to set email alerts
|

Current Progress of CAR-NK Therapy in Cancer Treatment

Abstract: CD8+ T cells and natural killer (NK) cells eliminate target cells through the release of lytic granules and Fas ligand (FasL)-induced target cell apoptosis. The introduction of chimeric antigen receptor (CAR) makes these two types of cells selective and effective in killing cancer cells. The success of CAR-T therapy in the treatment of acute lymphoblastic leukemia (ALL) and other types of blood cancers proved that the immunotherapy is an effective approach in fighting against cancers, yet adverse effects, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 149 publications
0
6
0
1
Order By: Relevance
“…Various strategies are being employed to overcome these challenges, such as ex vivo pre-conditioning with cytokines, treatment with small molecules, NK cells engineering, or iPSC differentiation in NK cells. 47 , 63 , 65 In this respect, we envision that the combination of adapalene and docetaxel may be used as an alternative strategy to enhance the efficacy of allogenic infusion of NK cells or CAR-NK cell treatment in metastatic PCa patients. This combination of compounds could promote an increased migration of NK cells in the tumors, ultimately enhancing their antitumor activity in this cold tumor model.…”
Section: Discussionmentioning
confidence: 99%
“…Various strategies are being employed to overcome these challenges, such as ex vivo pre-conditioning with cytokines, treatment with small molecules, NK cells engineering, or iPSC differentiation in NK cells. 47 , 63 , 65 In this respect, we envision that the combination of adapalene and docetaxel may be used as an alternative strategy to enhance the efficacy of allogenic infusion of NK cells or CAR-NK cell treatment in metastatic PCa patients. This combination of compounds could promote an increased migration of NK cells in the tumors, ultimately enhancing their antitumor activity in this cold tumor model.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Moreover, it is well understood that CAR-NK cells present significant challenges in genetic manipulation, and their antitumor efficacy is limited by the short life of NK cells. 33 While earlier reports indicated that NK therapy had no significant side effects, such as cytokine release syndrome (CRS), Zhang et al recently published clinical data on the use of the third generation of CAR-NK cells (referred to as CCCR-NK92) and observed CRS in one patient. 34 Another class of immunotherapeutic modalities harnessing NK cells, known as NK cell engagers (NKCEs), has recently emerged and exhibited several advantages over the abovementioned strategies.…”
Section: Discussionmentioning
confidence: 99%
“…This feature of NK cells can be used as an anti-tumor strategy, particularly because tumor cells frequently exhibit downregulation or loss of HLA-I molecules ( Mehta and Rezvani, 2018 ). They also induce less CRS and ICANS than CAR-T therapy ( Pang et al, 2022 ). However, their lifespan is low so this therapy will require various doses of treatment to achieve maintained CR ( Khawar and Sun, 2021 ) and CAR-NK manufacturing is more challenging than CAR-T cell expansion.…”
Section: New Approaches For Car-t Cell Therapy In Amlmentioning
confidence: 99%